Widespread higher fractional anisotropy associates to better cognitive functions in individuals at ultra‐high risk for psychosis. Issue 18 (20th August 2019) - Kristensen, Tina D.; Mandl, René C. W.; Raghava, Jayachandra M.; Jessen, Kasper; Jepsen, Jens Richardt M.; Fagerlund, Birgitte; Glenthøj, Louise B.; Wenneberg, Christina; Krakauer, Kristine; Pantelis, Christos; Nordentoft, Merete; Glenthøj, Birte Y.; et al.
Abstract: In schizophrenia patients, cognitive functions appear linked to widespread alterations in cerebral white matter microstructure. Here we examine patterns of associations between regional white matter and cognitive functions in individuals at ultra‐high risk for psychosis. One hundred and sixteen individuals at ultra‐high risk for psychosis and 49 matched healthy controls underwent 3 T magnetic resonance diffusion‐weighted imaging and cognitive assessments. Group differences on fractional anisotropy were tested using tract‐based spatial statistics. Group differences in cognitive functions, voxel‐wise as well as regional fractional anisotropy were tested using univariate general linear modeling. Multivariate partial least squares correlation analyses tested for associations between patterns of regional fractional anisotropy and cognitive functions. Univariate analyses revealed significant impairments on cognitive functions and lower fractional anisotropy in superior longitudinal fasciculus and cingulate gyrus in individuals at ultra‐high risk for psychosis. Partial least squares correlation analysis revealed different associations between patterns of regional fractional anisotropy and cognitive functions in individuals at ultra‐high risk for psychosis compared to healthy controls. Widespread higher fractional anisotropy was associated with better cognitive functioning for individuals at ultra‐high risk for psychosis, but not for the healthy controls. Furthermore, patterns of cognitive functions were associated with an interaction‐effect on regional fractional anisotropy in fornix, medial lemniscus, uncinate fasciculus, and superior cerebellar peduncle. Aberrant associations between patterns of cognitive functions to white matter may be explained by dysmyelination.